2012
DOI: 10.1063/1.3700538
|View full text |Cite
|
Sign up to set email alerts
|

Chiral dynamics of the S11(1535) and S11(1650) resonances revisited

Abstract: Abstract. We analyze s-wave pion-nucleon scattering in a unitarized chiral effective Lagrangian including all dimension two contact terms. We find that both the S 11 (1535) and the S 11 (1650) are dynamically generated, but the S 31 (1620) is not. We further discuss the structure of these dynamically generated resonances.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
14
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 11 publications
3
14
0
Order By: Relevance
“…While we have to notice that spin symmetry of three-quark component of S 11 (1650) in the traditional quark model is expected to be the completely symmetric [3] S [43], which should weaken the transition between the three-quark component of S 11 (1650) and the present obtained N ss (1661). In addition, as we can see in Table III, N ss (1661) should couple strongly to ηN and KΛ channels, this is consistent with the large branching ratio of the N * (1535) resonance to ηN channel [31], and the strong coupling of N * (1535) to KΛ channel predicted by isobar model [16] and chiral perturbation theory [22]. One may notice that non-vanishing coupling constant of N * (1650) to KΣ channel was reported in a very recent work [45], while as we can see in Ref.…”
supporting
confidence: 82%
See 1 more Smart Citation
“…While we have to notice that spin symmetry of three-quark component of S 11 (1650) in the traditional quark model is expected to be the completely symmetric [3] S [43], which should weaken the transition between the three-quark component of S 11 (1650) and the present obtained N ss (1661). In addition, as we can see in Table III, N ss (1661) should couple strongly to ηN and KΛ channels, this is consistent with the large branching ratio of the N * (1535) resonance to ηN channel [31], and the strong coupling of N * (1535) to KΛ channel predicted by isobar model [16] and chiral perturbation theory [22]. One may notice that non-vanishing coupling constant of N * (1650) to KΣ channel was reported in a very recent work [45], while as we can see in Ref.…”
supporting
confidence: 82%
“…Meanwhile, it is claimed that the sea quark-antiquark pairs contribution to properties of nucleon should be significant [13][14][15]. Besides, it is shown that the strangeness components in N * (1535) should account for the mass ordering of N * (1440), N * (1535), and Λ * (1405) [16], and the strong coupling of N * (1535) to the strangeness channels [17][18][19], which are consistent with the predictions of the chiral perturbation theory [20][21][22]. In addition, it is shown that data for the electromagnetic and strong decays of N * (1535) can also be well fitted by taking the strangeness contributions into account [23][24][25].…”
Section: Introductionsupporting
confidence: 68%
“…Yet one pole disappeared when the offshell corrections were switched on, and only one Λ(1405) survived. This contradicts [15,33]; in their ansatz, off-shell effects were found to be small and two poles were present. Revai [34,35] suggests that the two-pole structure is a consequence of the on-shell factorization approximation; without this approximation, only one pole was found.…”
Section: Introductionmentioning
confidence: 89%
“…While this can, a posteriori, deliver an improved description of the transition form factor, questions of how to bring models with hadronic degrees of freedom and quark/gluonic degrees of freedom conceptually together remain a challenge. Methods like chiral unitary approaches use only hadrons as degrees of freedom and have been used to study and predict meson-baryon dynamics [53,54].…”
Section: Pos(hadron2017)010mentioning
confidence: 99%